Screening of Mutants Related to the C4 Photosynthetic Kranz Structure in Foxtail Millet - Luo, Mingzhao; Zhang, Shuo; Tang, Chanjuan; Jia, Guanqing; Tang, Sha; Zhi, Hui; Diao, Xianmin (Frontiers in Plant Science, 2018)
C4 plants exhibit significantly higher photosynthetic, water and nutrient use efficiency compared with C3 plants. Kranz anatomy is associated with many C4 plants in which bundle sheath cells surround the veins and are themselves surrounded by mesophyll cells. This specialized Kranz anatomy is elucidated as an important contributor to C4 photosynthetic activities in C4 plant. Characterizing the molecular basis of Kranz structure formation has become a key objective for studies of C4 photosynthesis. However, severe mutants that specifically disrupt Kranz anatomy have not been identified. In this study, we detected 549 stable ethyl methane sulfonate-induced foxtail millet (cultivar Yugu1) mutants related to leaf development and photosynthesis among 2,709 mutants screened (M3/M4 generation). The identified mutants included 52 that had abnormal leaf veins (with abnormal starch accumulation based on iodine staining). Each of the 52 mutants was characterized through an analysis of leaf morphology, and through microscopic observations of leaf tissue sections embedded in resin and paraffin. In total, 14 mutants were identified with abnormal Kranz structures exemplified by small bundle sheath cell size. Additional phenotypes of the mutants included poorly differentiated mesophyll and bundle sheath cells, increased vein density and the absence of chloroplasts in the bundle sheath cells. Kranz structure mutations were accompanied by varying leaf thickness, implying these mutations induced complex effects. We identified mutations related to Kranz structure development in this trial, which may be useful for the mapping and cloning of genes responsible for mediating Kranz structure development.